Capture-based aquaculture : (Food and Agriculture Organization of the United nations, 2008)
Capture-based aquaculture makes use of wild fish and fishery resources in its production systems. Focusing on this subject, this document addresses selected key issues of sustainability in relation to current global aquaculture practices and developments. It includes two review papers on the use of wild resources, one covering social and economic aspects and the other on environmental and biodiversity issues, as well as ten papers on selected marine and freshwater species used in capture-based aquaculture.